Respuestas

2013-10-11T06:58:28+02:00
T = tensión
g = gravedad
p = peso = m g
m = masa
a = aceleración
*cuando la peso es mayor q la tensión:
   p - t = m a                 t= - ( ma - p )
                                   t= - ( ma - mg )
                                   t= - m ( a - g )
*cuando la tensión es mayor q el peso:
t - p = m a             ó             t =ma + p
                                           t = ma+mg
                                           t = m (a + g)
*cuando el peso y la tensión son iguales:
p = t